Sharenting on Instagram: abuse of the presence of minors in advertising - Fernández Blanco, Elena (2024)
The exposure of minors on social media by influencer mothers and fathers is becoming an increasingly common practice, especially on Instagram. Sharenting (a combination of "share" and "parenting"), understood as the sharing of information and photos of children on social media, raises numerous ethical, legal, and advertising-related questions. The digital footprint of minors and its potential effects are intertwined with the practice of influencer parents who use their children's images to promote brands and products. The objective of this study is to contribute to the research on sharenting in connection with influencer marketing, specifically focusing on mothers and fathers who use their children to create advertising content. The study aims to verify the presence of brands targeting minors in their parents' posts, analyze the use of minors' rights to image and privacy by their parents, and determine whether it complies with legal spanish advertising regulations. The presence of minors and brands in a sample of 89 influencer mothers and fathers on Instagram is analyzed through content analysis (363 posts from August 20th to September 20th, 2023, and 295 stories). The results indicate an extremely high presence of minors in posts by influencer mothers and fathers, and they often serve as vehicles for brands (with 96.71% of mothers' posts featuring brands), although fewer than 15% of these are identified as advertisements. The conclusions highlight the misuse of minors' images and privacy on Instagram by their influencer parents for advertising purposes.